Instructional sensitivity in vocational education. (February 2018) - Deutscher, Viola; Winther, Esther
Abstract: Apprentices' performance after vocational educational training (VET) is commonly attributed to the effectiveness of the training. This implies the assumption that learners' development of vocational knowledge and ability is significantly affected by vocational instruction. However, the few analyses that have been made of instructional sensitivity within the general school-based educational system, have in most cases shown little or no effect of instruction (time in school) on performance in assessments. The question as to whether, and to what extent, VET in adult education is effective (in the sense that it fosters the development of vocational knowledge and ability), as well as the related question—whether we are able to track the resulting learning progress with adequate measures (i.e., assessments)—has hardly been investigated. In the present study, we propose modeling of instructional sensitivity via differential item functioning (DIF), and apply this method to a sample of n = 534 apprentices. We find that during vocational instruction, apprentices significantly improved their performance in an assessment of vocational knowledge and ability, and that we were able to track these changes in the quality of their abilities over the span of a three year initial VET program: that is, the first program of vocational study in which apprentices become qualified to work in a given trade. Moreover, with this proposed method, it is possible to identify items that are particularly sensitive to instruction and that appear therefore to be amenable to the future development of vocational assessments. Highlights: An expedient method to detect instructional sensitivity is differential item functioning (DIF). Apprentices significantly improve their performance over the span of initial VET. The more generic the assessed knowledge and ability, the less sensitive it is to instruction. Items that are specific to a vocational domain are especially sensitive to instruction.